‘O Our India!’: Towards a Reassessment of Sir Edwin Arnold - Robinson, Catherine (Religions of South Asia, 2010)
Sir Edwin Arnold (1832–1904), a now neglected figure, was once honoured and revered. Focusing on Arnold’s varied writings on Indian themes, this article presents a case for reassessing his role and importance, concentrating on his contribution towards disseminating knowledge of Indian religions to Western readers and particularly his influence upon Buddhism both in terms of Western attitudes and Eastern responses. It applies Said’s theory of ‘Orientalism’ to analyse Arnold’s life and work, thereby illustrating some of the strengths and weaknesses of Said’s approach as well as some of the complexities of Arnold’s character. Arnold is shown to have pursued a popularizing project yet appealed to scholarly findings, discussed the distinctions between ‘East’ and ‘West’ but also their continuities and expressed an overt imperial ideology though critiquing it in certain respects. Addressing one allegation levelled against Said, that he does not acknowledge the depth and breadth of the ‘East’s’ impact upon the ‘West’, this article explores a range of issues centred on The Light of Asia and Buddhism. Thus it demonstrates how Arnold changed Western attitudes towards Buddhism and, through raising consciousness of the state of Bodhgaya, stimulated a campaign that was to have far-reaching consequences for ‘modern Buddhism’.